CARBON SEQUESTRATION AND LIPID ACCUMULATION OF CHLORELLA VULGARIS AND SPIRULINA PLATENSIS IN ZARROUK AND BOLD BASAL MEDIUM - Husna, Annisa
Microalgae is a potential biological agent for global warming mitigation through carbon sequestration. This photosynthetic organism absorbs carbon dioxide from the air and converts it to organic products, such as carbohydrate, protein, pigment, and lipid. Microalgae’s photosynthetic efficiency is 10-50 times higher than terrestrial plants thus making it a potential biological agent for carbon sequestration. Coculture of Chlorella vulgaris and Spirulina platensis is reported to increase growth, carbon absorption, and lipid accumulation in microalgae. This research has the purpose of evaluating the performance of Spirulina platensis and Chlorella vulgaris coculture in autotrophic system with Zarrouk and Bold Basal Medium (BBM) as growth mediums. Ratio of Zarrouk and BBM in the coculture variations were 25:75; 50:50; and 75:25 (v/v). Performance of these cocultures were also compared with S. platensis monoculture in Zarrouk 100% and C. vulgaris monoculture in BBM 100%. Microalgae was cultivated for 16 days in one liter glass bottle with 0,4 l/min aeration. Biomass concentration measurement was done in every two days. This parameter was used to determine kinetics parameter maximum specific growth rate and maximum biomass concentration. Carbon absorption rate was determined through the calculation of biomass’ productivity, biomass’ carbon content, and the ratio between the molecular weight of carbon and carbon dioxide. Lipid extraction was conducted with the Bligh and Dyer method. Result showed the maximum specific growth rate for S. platensis in Zarrouk monoculture, C. vulgaris in BBM monoculture, and S. platensis and C. vulgaris coculture in Zarrouk:BBM (25:75; 50:50; and 75:25 v/v) was 0,28; 0,30; 0,26; 0,21; dan 0,25 /day, respectively, with the highest value achieved by C. vulgaris monoculture as much as 0,30 /day. There was no significant difference in the growth within all groups. The maximum CO2 absorption rates was 0,605 0,11; 0,120 0,01; 0,275 0,08; 0,210 0,05; 0,259 0,05 gCO2/l/day and the amount of CO2 absorbed after 16 days was 3,71 0,22; 0,87 0,03; 1,90 0,12; 1,72 0,20; and 1,79 0,11 gCO2/0,8 liter medium for S. platensis in Zarrouk monoculture, C. vulgaris in BBM monoculture, and S. platensis and C. vulgaris coculture in Zarrouk:BBM (25:75; 50:50; and 75:25 v/v), respectively. The highest CO2 absorption was achieved by S. platensis monoculture with CO2 absorption rate of 0,605 0,11 gCO2/l/day and the amount of CO2 absorbed after 16 days of 3,71 0,22 gCO2/0,8 L medium. There was significant difference in CO2 absorption within all groups but no significance difference within the coculture groups. Lipid accumulations in S. platensis in Zarrouk monoculture, C. vulgaris in BBM monoculture, and S. platensis and C. vulgaris coculture in Zarrouk:BBM (25:75; 50:50; and 75:25 v/v) was 0,16 0,04; 0,21 0,04; 0,11 0,01; 0,15 0,07; 0,13 0,01 (glipid/gbiomass). The highest lipid accumulation is achieved by C. vulgaris monoculture which was 0,21 0,04(glipid/gbiomass). There was no significant difference in lipid accumulation within all groups. In brief, the coculture of S. platensis and C. vulgaris sequesters more carbon than the C. vulgaris monoculture but less than the S. platensis monoculture. The highest growth and lipid accumulation is achieved in the C. vulgaris monoculture compared to the S. platensis monoculture or the S. platensis and C. vulgaris coculture